Experimental and numerical analyses of the effectiveness of high‐frequency peening processes. Issue 1 (January 2017) - Mangerig, Ingbert; Kroyer, Robert; Koller, Matthias
Abstract: Dedicated to Prof. Dr. Akimitsu Kurita on his 70th birthday To assess fatigue behaviour, experimental tests were conducted on material specimens furnished with hammer peening tracks, with two different types of treatment being employed. The results of fatigue tests on treated specimens were compared with those of untreated specimens and assessed. Non‐linear analyses with the FE program ADINA, taking into account the stress–distortion behaviour of a material subjected to fatigue, were conducted as part of the test concept, specimen analysis, evaluation of the test results and probing the mode of action of both techniques.